Molecular Detection and Characterization of Hemoplasmas in the Pudu (Pudu Puda), a Native Cervid from Chile - Vergara-Egert, P; Moreira-Arce, D (Wildlife Disease Association, Inc., 2022)
Hemotropic mycoplasmas cause hemolytic anemia in a variety of wild and domestic mammals. Despite growing evidence about their widespread presence and genetic diversity in wildlife, their presence has never been investigated in Chilean artiodactyls. We aimed to describe the presence and diversity of hemoplasmas in pudus (Pudu puda), a small cervid native to Chile. Hemoplasma infection was assessed in blood samples from 43 wild and 33 captive pudus from central and southern Chile by direct sequencing of the 16S rRNA gene. We detected hemoplasmas in 13%, with no statistical differences between wild (19%) and captive animals (6%). A sequence closely related to Mycoplasma ovis was present both in wild (14%) and captive (6%) pudus. Two previously undescribed sequences, classified in a clade including hemoplasmas from carnivores, were found in one wild pudu each. This study presents the first evidence of the presence of M. ovis-like organisms in Chile and of the susceptibility of pudus to infection with hemoplasmas. Further research is needed to understand the pathologic consequences of this pathogen for pudus, its effects at the population level, and their potential impact on the health small ruminants and other wildlife species in Chile. © Wildlife Disease Association 2022.